The Effectiveness of Mulberry Leaf Extract Supplementation on C-Reactive Protein (CRP) Levels in Sprague Dawley Rats Hyperlipidemia Model - Yugi Hari Chandra Purnama; Emi Eliya Astutik (Journal of Nursing Periodic, 2026)
Introduction: Hyperlipidemia is a major risk factor for cardiovascular disease and is closely associated with chronic inflammation, reflected by elevated C-reactive protein (CRP). Although statins effectively reduce lipid levels, their long-term use may produce adverse effects, highlighting the need for evidence-based complementary herbal therapies. Mulberry leaf (Morus alba L.) contains flavonoids and other bioactive compounds with hypolipidemic, antioxidant, and anti-inflammatory properties. This study evaluated the effect of mulberry leaf extract supplementation on CRP levels in Sprague Dawley rats with hyperlipidemia. Methods: A true experimental pretest-posttest control group design was conducted using 24 male Sprague Dawley rats assigned to four groups (n = 6): normal, negative control, positive control (simvastatin), and treatment (Morus alba leaf extract, 600 mg/kg body weight/day). Hyperlipidemia was induced with a high-fat diet for eight weeks, followed by five weeks of intervention. Serum CRP levels were measured using a rat CRP ELISA kit. Data were analyzed using paired t-tests, Kruskal-Wallis, and Mann-Whitney post hoc tests (p < 0.05). Results: CRP levels decreased significantly in both the simvastatin and mulberry leaf extract groups (p < 0.001). Delta CRP values differed significantly among groups (p < 0.001), confirming that mulberry leaf extract effectively reduced systemic inflammation. Conclusion: Mulberry leaf extract shows promise as an evidence-based complementary herbal therapy for reducing inflammation and preventing cardiovascular complications, supporting its integration into complementary nursing interventions for cardiovascular disease prevention